Symbiotic Properties of Phage Resistant Mutants of Rhizobium sp. of Vigna aeon itifo lia - Gupta, Deepak; Rmkrishna, K (Annals of Arid Zone, 2016)
Spontaneously ansmg phage resistant mutants were isolated from a streptomycin resistant mutantÂ· of Vigna aconitifolia Rhizobium MR-4 I, susceptible to two different lytic viruses, V1 producing turbid plaques.and V2 producing clear plaques. Forty mutants resistant to VI (group I) and the. other 40 mutants 'resistant to V2 (group II) were examined for their in vivo nitrate reductase activity. In both the groups mutants ranged from complete lack of nitrate reduction to 25- fold higher reduction. Nodules produced by the mutants of the two groups were often significantly higher than the parent. Two mutants of group I and 6 mutants of group II were significantly better than parent in symbiotic effectiveness. None of the mutants of the two groups was ineffective.